Implementing information technology governance : models, practices, and cases - Van Grembergen, Wim (IGI Pub., 2008)
"This book presents insight gained through literature reviews and case studies to provide practical guidance for organizations who want to start implementing IT governance or improving existing governance models, and provides a detailed set of IT governance structures, processes, and relational mechanisms that can be leveraged to implement IT governance in practice"--Provided by publisher.